PKM MENINGKATKAN EKONOMI DENGAN MENGATASI MASALAH SAMPAH MELALUI BANK SAMPAH - Rahayu, Luis Fiska (Nindikayla Institute, 2022)
Minister of Environment and Forestry Regulation 14 of 2021 concerning Waste Management in Waste Banks has the intention that Waste Management needs to be carried out in a comprehensive and integrated manner from upstream to downstream with a circular economy approach by the central government, regional governments and the community, so as to provide economic benefits, be healthy for the community, and safe for the environment. LHK Ministerial Regulation 14 of 2021 concerning Waste Management in Waste Banks explains that waste is the residue of human daily activities and/or natural processes in solid form. Waste Management is a systematic, comprehensive, and sustainable activity that includes waste reduction and handling. Waste Bank is a facility to manage waste with the 3R principle (Reduce, Reuse, and Recycle), as a means of education, behavior change in waste management, and the implementation of a Circular Economy, which is formed and managed by the community, business entity, and/or local government